1954
DOI: 10.3382/ps.0331130
|View full text |Cite
|
Sign up to set email alerts
|

Fat Studies in Poultry

Abstract: A S PART of an investigation into the i at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1955
1955
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Biely, March and Silvestrini (1954) have reported that an alkyl-aryl sulfonate fed at 0.1% of a basal ration of laying hens promoted better feed efficiency for egg production.…”
mentioning
confidence: 98%
“…Biely, March and Silvestrini (1954) have reported that an alkyl-aryl sulfonate fed at 0.1% of a basal ration of laying hens promoted better feed efficiency for egg production.…”
mentioning
confidence: 98%